Role of 'Student‐to‐Student Local Analgesia Administration' on undergraduate students' opinions regarding 'Pain‐Free Local Analgesia Technique' in children. (28th March 2013) - Kuscu, O. O.; Kucuktepe, C.; Caglar, E.; Cildir, S. K.; Hacinlioglu, N.; Sandallı, N.
Abstract Aim To examine the role of 'student‐to‐student local analgesia administration' on undergraduate dental students' opinions regarding pain‐free local analgesia techniques in children. Methods Grade 3 (n:29), Grade 4 (n:59) and Grade 5 students (n:28) of Yeditepe University, School of Dentistry, Istanbul, Turkey participated in the study. Informed consent and ethical approval were obtained. Students' opinions were evaluated by means of a short survey administered before and after educational activities. Activities were provided in a didactic manner (theoretical, practical and clinical stages) and lasted for 6 months. Theoretical lectures on 'pain‐free local analgesia techniques in children' were given to all classes. In the practical stage, 3rd and 4th grade students were paired and performed infiltration analgesia on each other according to the lectured technique. In the final clinical stage, 4th and 5th grade students were supervised, whilst administering the technique on children during their clinical training. Results Before the activities, only 40% of students believed in the possibility of pain‐free local analgesia in children, whereas after the educational activities, the percentage had risen to 68% (P = 0.0001). A significant difference was observed between the opinions of 4th grade students who attended the practical stage and 5th grade students who did not. Conclusion The role of 'student‐to‐student local analgesia administration' was found to be significant in changing undergraduate students' opinions about pain‐free dental injections in children.